(untitled) (Indian Journal of Chemistry (IJC), 2025)
Spilanthol, a bioactive compound from Acmella oleracea, was evaluated for its potential as a COX-2 inhibitor through computational and experimental methods. The study utilized Lipinski’s rule of 5, Molinspiration scoring, molecular docking, MM-GBSA/MM-PBSA calculations, and molecular dynamics simulations to assess Spilanthol’s drug-likeness, binding affinity, and interaction stability with COX-2. Spilanthol met several criteria of the Lipinski rule, indicating favorable drug-like properties but showing high hydrophilicity, which could impact membrane permeability. The Molinspiration analysis revealed that Spilanthol has significant enzyme inhibition potential, though it was less effective against other targets such as GPCRs and kinases. Molecular docking results demonstrated a strong binding affinity with COX-2, evidenced by a binding energy of -7.50 kcal/mol and an inhibition constant of 3.21 µM. MM-GBSA/MM-PBSA calculations further supported these findings with negative binding energies, indicating stable interactions. Molecular dynamics simulations highlighted significant conformational changes in COX-2 upon Spilanthol binding, as reflected by alterations in RMSF values. These results suggest that Spilanthol effectively binds to and inhibits COX-2, offering potential as a natural anti-inflammatory agent. The compound’s interaction profile and stability within the COX-2 active site emphasize its promise for development as an alternative to synthetic COX-2 inhibitors, potentially providing effective pain and inflammation relief with reduced side effects.